THE ROLE OF PERCEIVED ORGANIZATIONAL SUPPORT AND EMPLOYEE ENGAGEMENT IN OPTIMIZING EMPLOYEE PERFORMANCE - Ali Koesoema Wardhana; Rabitha Fazira (Universitas Muhammadiyah Tangerang, 2026)
Employee performance is a crucial factor determining organizational success. The declining trend in sales target achievement at PT Tiga Pilar Doa Suplindo indicates performance issues presumably related to negative perceptions of organizational support and low employee engagement. This study aims to analyze the influence of perceived organizational support (POS) and employee engagement on employee performance and identify the dominant predictor. This quantitative research employed total sampling involving all 41 employees. Data were collected through a validated and reliable Likert-scale questionnaire and analyzed using descriptive statistics, classical assumption tests, and multiple linear regression with SPSS version 24. The findings reveal that POS and employee engagement simultaneously have a positive and significant effect on employee performance. Partially, employee engagement is proven to have a positive and significant effect on employee performance, while POS shows a positive but non-significant effect. These findings indicate that employee engagement is a more dominant predictor in improving performance compared to POS. The novelty lies in examining the simultaneous influence of POS and employee engagement within the Indonesian distribution company context and identifying employee engagement as the dominant performance predictor. This study contributes theoretically to human resource management literature and provides practical implications for designing engagement-based performance improvement interventions.